Need Analysis for Identifying ESP Materials for Nursing Science Study Program STIK Bina Husada Palembang - Agus Wahyudi (Formosa Journal of Applied Sciences, 2022)
Material development is one of the important factors that determine the success of the language teaching and learning process. Teaching materials are a key component in language programs. English for Specific Purposes (ESP) is generally interpreted as an approach to learning English based on the goals/needs of the learner. In this study, the researcher used a descriptive method. The participants of this study were 7th semester students of the Nursing Science Study Program at STIK Bina Husasa Palembang, there were 58 students who had filled out a complete questionnaire, consisting of 11 males and 47 females. The instrument used is a questionnaire, The result showed student’s personal reasons for studying English was to be able to communicate in English fluently. 28% of the students answered to know and understand the grammar accurately, and 17% stated for working purposes. Further, majority of the students wanted to master their speaking skill at the end the program, followed by reading and speaking skills. 9% of the students wanted to master the listening skill and 9% of the students wanted to master all English aspects. The data generated from student questionnaires and interviews with the head of the nursing study program at STIK Bina Husada Palembang have explained several issues that need to be considered because the results of the answers offered offer significant suggestions for the development of English materials at STIK Bina Husada Palembang.